Triflumuron induces genotoxicity in both mice bone marrow cells and human Colon cancer cell line. (23rd July 2020) - Timoumi, Rim; Amara, Ines; Ayed, Yossra; Ben Salem, Intidhar; Abid-Essefi, Salwa
Abstract: Triflumuron (TFM) is an insect growth regulator (IGR), an insecticide commonly used over the world. It is known for its several toxic manifestations, such as reprotoxicity, immunotoxicity and hematotoxicity, which could affect public health. However, studies that reveal its toxic effects on mammalians are limited. To reach this purpose, our study aimed to elucidate the eventual genotoxic effects of TFM in mice bone marrow cells and in HCT 116 cells after a short term exposition. TFM was administered intraperitoneally to Balb/C male mice at doses of 250, 350 and 500 mg/kg bw for 24 h. Genotoxicity was monitored in bone marrow cells using the comet test, the micronucleus test and the chromosome aberration assay. Our results showed that TFM induced DNA damages in a dose-dependent manner. This genotoxicity was confirmed also in vitro on human intestinal cells HCT 116 using the comet test. It was then asked whether this genotoxicity induced by TFM could be due to an oxidative stress. Thus, we found that TFM significantly decreased HCT 116 cell viability. In addition, it induced the generation of reactive oxygen species (ROS) followed by lipid peroxidation as revealed by the increase in the malondialdehyde (MDA) levels. Similarly, the activation of the antioxidant enzymes (catalase and superoxide dismutase) was also observed. Our results indicated that, in our experimental conditions, TFM had a genotoxic effect on bone morrow cells and in HCT 116 cells. Moreover, we demonstrated that this genotoxicity passes through an oxidative stress.